Micro and Macro Structural Investigations on Welded Joints of Composite Truss Steel Concrete Beams - Silvia Caprili; Walter Salvatore; Renzo Valentini (Advances in Materials Science and Engineering)
The results of an experimental test campaign including micro and macro investigations on welded joints typically used in Composite Truss Steel-Concrete beams are presented. The research was carried out with the aim of assessing the relevance of welding effects on the mechanical performance of different typologies of steel grades that can be used to realize the internal truss steel system, connected to the bottom steel plate used with the double structural and formwork function. Two different steel typologies were adopted for the steel truss: the “traditional” structural micro-alloyed steel, normally used for composite steel-concrete elements, and the typical reinforcing steel with TempCore® structure, achieved through the application of two-phase thermomechanical treatment of quenching and tempering. The interest in the possibility of adopting reinforcing steel for the internal truss arises from its potential economic benefit, finding its justification in the intermediate condition in which this structural typology lies, between composite steel-concrete and ordinary reinforced concrete buildings. Welding has a strong impact on such reinforcing steel material, resulting in relevant drops of ductility and brittle failure usually taking place in correspondence of the heat-affected zone. So, it is advisable to refrain from using such steel grade, especially in constructions in seismic-prone areas, where ductility is a major influencing and design factor.